Pengaruh Jenis Prebiotik terhadap Kualitas Yogurt Probiotik - Ekawati Purwijantiningsih (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
Prebiotics are variety of nondigestible carbohydrates that help promote the growth of good bacteria in the intestines. Prebiotics are found naturally in legumes, vegetables, fruits and tubers. Soybean, banana and tapioca are supposed to have potential as prebiotics, promote a healthy digestive system and reduce the growth of harmful bacteria. Soybean, banana and tapioca were investigatedon their abilities to promote the quality of probiotic yogurt. Soybean flour addition to probiotic yogurt most potential to promote nutrition value and lactic acid bacteria viability. The most preference of probiotic yogurt by panelists is probiotic yogurt added tapioca.